Dynamics and efficiency of planetary gear sets for hybrid powertrains. (April 2016) - Mohammadpour, M; Theodossiades, S; Rahnejat, H
The paper presents a tribo-dynamic model for planetary gear sets of hybrid-electric-vehicle configurations. The model comprises a six degree-of-freedom torsional multi-body dynamic system, as well as a tribological contact model in order to evaluate the lubricant film thickness, friction and efficiency of the meshing gear teeth contacts. The tribological model takes into account the non-Newtonian, thermal-mixed elastohydrodynamic regime of lubrication. Analysis is performed for a hybrid electric C-segment vehicle. The simulated conditions correspond to cases of power supplied by either the engine or the electric motor. The results illustrate that in the electric motor drive mode, improved noise, vibration and harshness refinement would be expected, whereas better transmission efficiency is achieved in the internal combustion engine drive mode.